Driving is a Risky Business. Issue 4 (28th July 2021) - Bonnett, Laura
Abstract: Lapses in concentration while driving can be fatal, so if a person experiences a seizure – whether behind the wheel or not – UK authorities require that person to take time off driving until the risk of another seizure falls below a set threshold. But how much time off is required? Laura Bonnett explains how statistics helped find an answer